Identification and Expression of Cephamycinase bla(CMY) Genes in Escherichia coli and Salmonella Isolates from Food Animals and Ground Meat - Zhao, Shaohua (American Society for Microbiology, 2001)
Twenty-one Salmonella and 54 Escherichia coli isolates, recovered from food animals and retail ground meats, that exhibited decreased susceptibilities to ceftiofur and ceftriaxone were shown to possess a bla(CMY) gene. The bla(CMY-4) gene was identified in an E. coli isolate recovered from retail chicken and was further shown to be responsible for resistance to cephalothin, ampicillin, and amoxicillin-clavulanic acid and elevated MICs of ceftriaxone, cefoxitin, and ceftiofur.